2017
DOI: 10.7717/peerj.4116
|View full text |Cite
|
Sign up to set email alerts
|

Skin temperature and reproductive condition in wild female chimpanzees

Abstract: Infrared thermal imaging has emerged as a valuable tool in veterinary medicine, in particular for evaluating reproductive processes. Here, we explored differences in skin temperature of twenty female chimpanzees in Budongo Forest, Uganda, four of which were pregnant during data collection. Based on previous literature in other mammals, we predicted increased skin temperature of maximally swollen reproductive organs of non-pregnant females when approaching peak fertility. For pregnant females, we made the same … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The preliminary results indicate the potential of thermal imaging in late-pregnancy diagnosis. Physiologically, the more progressing days of pregnancy correlate with an increase of the amount of vascularization and tissues' formation and all of these will bring consequences to potential increase of temperature (Dezecache et al, 2017). Our findings support the above physiological entity.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The preliminary results indicate the potential of thermal imaging in late-pregnancy diagnosis. Physiologically, the more progressing days of pregnancy correlate with an increase of the amount of vascularization and tissues' formation and all of these will bring consequences to potential increase of temperature (Dezecache et al, 2017). Our findings support the above physiological entity.…”
Section: Resultssupporting
confidence: 82%
“…Promoting non-invasive methods in research and routine husbandry procedure are one of the best practices (NC3Rs 2018). Providing non-invasive measurements to measure physiological values to conventional clinical examination that require chemical restrains, are also considered as refinement (Dezecache et al, 2017;Hau and Schapiro, 2004). The thermal imaging may be one of the non-invasive criteria which provide a real-time measurement of the basic physiological value of body temperature thus useful to estimate the health status (Cilulko and Janiszewski, 2013;Christiansen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal imaging has previously been calibrated with standard methods of measuring physiological activity, such as heart rate (electrocardiography), respiration (piezoelectric thorax stripes), skin conductance (galvanic skin response) or skin temperature (nasal thermistors) 24 . Furthermore, in wild chimpanzees the method has been used in two pilot studies investigating responses to vocalisations 26 and differences in females’ reproductive states 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Most wildlife application of thermal imaging are based upon locating and identifying animals in darkness (Bipad-Cilulko et al 2013). Utilization of the technology in stress and behavioral studies have been reported in songbirds , waterfowl (Austin et al 2016), flying squirrels (Horton et al 2015) and various primates (Kano et al 2015, Ioannou et al 2015, Dezecache et al 2017.…”
Section: Introductionmentioning
confidence: 99%